Implementasi Internet of Thing (IOT) untuk Monitoring dan Pengaman Beban Listrik 3 Phase Menggunakan Fuzzy Sugeno - Siregar, Rais Sardi; Ikhsan, Muhammad (Jurnal Algoritma, 2025)
This study aims to design and implement an Internet of Things (IoT) system based on the Fuzzy Sugeno method for monitoring and securing three-phase electrical loads. The study was conducted quantitatively by collecting data from direct testing of the system being built. The system utilizes the PZEM-004T sensor to measure electrical parameters such as current and power in real-time on each phase, which are then analyzed using fuzzy logic to determine automatic security measures. The test results show that the system is able to detect load conditions with a voltage measurement accuracy level of 99.76% on the R phase, and 99.87% on the S and T phases. For current and power measurements, the accuracy is in the range of 97.13% to 98.09%. The system also successfully applies nine fuzzy rules to make decisions on load conditions, producing security outputs through relays automatically. In addition, the implementation of Blynk application-based monitoring allows users to monitor electrical parameters remotely effectively. Overall, the research results prove that the application of IoT with Fuzzy Sugeno can improve the efficiency, security, and reliability of three-phase electrical systems, while providing smart solutions in energy maintenance and management.